Progress in Additive Manufacturing of Energetic Materials: Creating the Reactive Microstructures with High Potential of Applications. Issue 8 (29th May 2019) - Muravyev, Nikita V.; Monogarov, Konstantin A.; Schaller, Uwe; Fomenkov, Igor V.; Pivkina, Alla N.
Abstract: The modern "energetic‐on‐a‐chip" trend envisages reducing size and cost while increasing safety and maintaining the performance of energetic articles. However, the fabrication of reactive structures at micro‐ and nanoscales remains a challenge due to the spatial limitations of traditional tools and technologies. These mature techniques, such as melt casting or slurry curing, represent the formative approach to design as distinct from the emerging additive manufacturing (3D printing). The present review discusses various methods of additive manufacturing based on their governing principles, robustness, sample throughput, feasible compositions and available geometries. For chemical composition, nanothermites are among the most promising systems due to their high ignition fidelity and energetic performance. Applications of reactive microstructures are highlighted, including initiators, thrusters, gun propellants, caseless ammunition, joining and biocidal agents. A better understanding of the combustion and detonation phenomena at the micro‐ and nanoscale along with the advancement of deposition technologies will bring further developments in this field, particularly for the design of micro/nanoelectromechanical systems (MEMS/NEMS) and propellant grains with improved performance. Abstract :